Jane [videorecording (DVD)] - Morgen, Brett (National Geographic, 2017)
Looks back at Jane Goodall's career as a primatologist, animal rights advocate, and environmental activist. Comprised of present-day interview segments with Goodall and archival footage of her work studying chimpanzees at Tanzania's Gombe National Park shot by Hugo van Lawick in the 1960s for National Geographic.